Dietary administration impact of olive pulp on growth performance, metabolic profile, immune status, and antioxidant potential of gilthead seabream (Sparus aurata L.) - Bahi, Abir; Bhaskaracharya, Raman; Esteban, Maria Angeles; Guardiola, Francisco A. (Frontiers in Sustainable Food Systems, 2024)
The use of natural immunostimulants in aquaculture is intended to foster overall health and bolster resilience against diseases in farmed fish populations. It constitutes a crucial strategy that can contribute to securing the sustainability of the aquaculture industry, and it is an area that warrants ongoing exploration and development. Therefore, the aim of the present work was to evaluate the effect of dietary administration of olive pulp on growth rate, metabolic profile, serum antioxidant potential, and humoral and cellular innate immune parameters of gilthead seabream (Sparus aurata L.). For this, fish were fed control diet or olive pulp enriched diets (50, 100, and 200 mg kg feed -1 ) for 4 weeks. Our results demonstrated that the highest inclusion level improved the growth rates and the biological antioxidant potential in the serum of fish. However, after 4 weeks of feeding, most of the assayed metabolic parameters (Ca 2+ , TP, ALB, K + and Na + ) were increased in the serum of fish fed with a diet containing the lowest level of olive pulp (50 mg kg feed -1 ). Regarding the innate immune parameters, the IgM levels decreased in the serum of fish fed 50's diet after 2 and 4 weeks of trial. However, the serum of fish fed with diets containing 100 and 200 showed an increase in hemolytic complement activity after 2 weeks whilst this increase was only sustained in the 200's group after 4 weeks. After two weeks of feeding, the serum of the fish showed an increase in peroxidase activity due to the highest olive inclusion. Concerning cellular innate parameters, peroxidase activity, respiratory burst, and phagocytic ability were increased in head-kidney leucocytes of fish fed 100's diet at 2 weeks compared to values from control fish. These results suggest that the administration of olive pulp-enriched diets can benefit fish growth, antioxidant, and immune status of gilthead seabream.